2021
DOI: 10.1007/s42452-021-04602-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and durability assessment of cement-based and alkali-activated coating mortars in an aggressive marine environment

Abstract: Coatings are used as practical solutions against the intrusion of corrosive ions into concrete structures, particularly, in the harsh marine environment. In the present study, the effectiveness of using cement-based and geopolymer-based coatings produced using by-product materials has been evaluated. Silica fume and GGBFS at their optimum dosages were incorporated into mortar mixtures as a cement replacement, and mixtures of NaOH or KOH and sodium silicate solutions were used in the alkali-activated mortars. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The bond strength between the substrate concrete and the geopolymer matrix is also important if it is to be used as a strengthening or repair material [100]. Lashkari et al [101] presented the investigation of geopolymer-based coating exposed to harsh environments along the Persian Gulf. It is reported that slag in geopolymer exposed to such environments has better ability to fill voids, which influences the lower effect of chloride ions.…”
Section: Geopolymers As a Strengthening Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bond strength between the substrate concrete and the geopolymer matrix is also important if it is to be used as a strengthening or repair material [100]. Lashkari et al [101] presented the investigation of geopolymer-based coating exposed to harsh environments along the Persian Gulf. It is reported that slag in geopolymer exposed to such environments has better ability to fill voids, which influences the lower effect of chloride ions.…”
Section: Geopolymers As a Strengthening Materialsmentioning
confidence: 99%
“…Reinforcing with fibers helps in controlling the drying shrinkage of geopolymers [101]. Guo et al [113] mentioned that the incorporation of fibers in geopolymers could also reduce cracks.…”
Section: Fiber-reinforced Geopolymers (Frg) Used As Unreinforced Maso...mentioning
confidence: 99%
“…In concrete structures, to prevent the concrete from the intrusion of corrosive ion coatings was used as a practical solution. Lashkari et al [21] have evaluated the effectiveness of utilizing geopolymer and cementbased coatings created using materials from the waste by-products. In alkali-activated mortars, the mixtures of sodium silicate, and potassium hydroxide (KOH) and sodium hydroxide (NaOH) were utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Nicoleta [24] prepared and tested fireproof inorganic coatings based on sodium silicate solution with intumescent additions, which sensibly reduced the rate of temperature increase (up to 75%) in the steel substrate. Salar Lashkari [25] found AAMs have shown better performance compared to cement-based mortars by evaluating the durability characteristics and mechanical properties of AAMs and cement-based coating mortars in the harsh environment of the Persian Gulf. Thus, the utilize of alkali activated materials coatings would minimize the accumulation of solid waste, those were defined as a sustainable material depend on economical and environmentally friendly [20][21][22].…”
Section: Introductionmentioning
confidence: 99%